2016
DOI: 10.1007/s13187-016-0993-6
|View full text |Cite
|
Sign up to set email alerts
|

Medical Knowledge Assessment by Hematology and Medical Oncology In-Training Examinations Are Better Than Program Director Assessments at Predicting Subspecialty Certification Examination Performance

Abstract: The Accreditation Council for Graduate Medical Education's Next Accreditation System requires training programs to demonstrate that fellows are achieving competence in medical knowledge (MK), as part of a global assessment of clinical competency. Passing American Board of Internal Medicine (ABIM) certification examinations is recognized as a metric of MK competency. This study examines several in-training MK assessment approaches and their ability to predict performance on the ABIM Hematology or Medical Oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Thirty-seven studies were ultimately included in our data extraction and subsequent pooled analysis (see Figure 1). 10–46…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies were ultimately included in our data extraction and subsequent pooled analysis (see Figure 1). 10–46…”
Section: Resultsmentioning
confidence: 99%
“…Test reliability is high (KR 20 >0.90) across administrations similar to national certifying exams [6]. In-training examination (ITE) scores have been reported to be better predictors of subsequent resident scores on subspecialty certification exams than ratings of medical knowledge from program directors [7]. Since the IM-ITE is a national, standardized exam residents take every year, the IM-ITE can serve as a measure of both knowledge of general IM and IM subspecialties.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from specialties such as hematology, infectious disease, and nephrology have shown that there are positive associations between ITE scores and board CEs scores, and ITE performance may be used to predict candidates' likelihood of success in a future certification attempt. [1][2][3] The need for an ITE for medical genetics and genomics residency programs was first discussed at the 2009 meeting of the Residency Program Directors. A small committee was formed to develop and implement the examination, which was administered from 2010 to 2012 through the University of Alabama at Birmingham.…”
Section: Introductionmentioning
confidence: 99%